Quality Analysis Using WebQual Method and Importance Performance Analysis (IPA) Case Study on Learning Management System (LMS) Indonesian Institute of Education (IPI) Garut - Yopi Nugraha (RISTEC : Research in Information Systems and Technology, 2022)
With the development of technology, there are also tools to help humans complete all work. For example, what students do in supporting lecture activities. Looking for references to increase knowledge of a course, see lecture tutorials and many others. Technology in learning activities that has been known is the use of a Learning Management System (LMS) which can make lecture activities via online or commonly called e-learning. Especially in the present era of the pandemic and the spread of the covid-19 virus, people are not allowed to leave the house let alone go to school, but learning cannot be abandoned so that e-learning activities cannot be avoided. The quality of the use of media for learning can affect the quality of learning as well, whether it can be a barrier to learning or on the contrary, it can actually be the main supporter in achieving achievement. Therefore, in this study, we will analyze the quality of the Learning Management System (LMS), especially those used by students at the Indonesian Institute of Education (IPI) Garut with the WebQual method by assessing a product or website based on user perceptions and Importance Performance Analysis (IPA) based on analysis. the quadrant. The results obtained are that the quality of the Learning Management System (LMS) has not been said to be good because there are many points that still need to be improved, such as information that is not up to date, ease of use and the most prominent can be seen from the monotonous appearance so that it can be used as material. evaluation to be able to reconstruct the design, update information and streamline the use of the Learning Management System (LMS) Indonesian Institute of Education (IPI) Garut.